THE IMPORTANCE OF PEARLS IN CONTINUOUS EDUCATION SYSTEM - Hasanova Sabohat Komil qizi (Journal Park Publishing, 2024)
While reading this article, you will learn about the methodological recommendations necessary for specialists, the mechanisms of excellent use of PIRLS in many fields. And throughout the article, you will witness that many aspects of PIRLS are revealed
Keywords: recommendations, requirements, educational process, opportunities, methodological recommendations PIRLS research, results and goals, rating, experts, independent education, mechanism.